Essentials of modern physics applied to the study of the infrared. - Hadni, Armand (International series of monographs in infrared science and technology, 1967)
Essentials of Modern Physics Applied to the Study of the Infrared covers topics about the essentials of modern physics. The book starts with the situation of research into the infrared and the problems to which it gives rise, and then discusses instrumentation in the infrared: optics, sources, receivers and electronics. The book describes the interaction between the infrared and matter within the framework of Lorentz's general theory and in the particular case of solids using Born's theory and introducing the notion of phonons. The region of the electromagnetic spectrum and the developments i.